Świat Arabski - charakterystyka i kierunki rozwoju gospodarczego - AL-Noorachi, Muzahim (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Presented material implies that the Arab World is diversified considering the environmental factors, human potential, financial capabilities, social and economic development level, political systems and economic development concepts. It is a monolith from the point of view of nationality, religion, language, culture and, to some extent, history. The above mentioned elements should constitute a strong foundation, on which it would be possible to build a strong and effective economic co-operation. However, as can be seen, it is a divided and disturbed world. In our opinion, the main obstacle in this respect lies in political and world outlook differences of elites in power. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 13-24